Leo Tolstoy - Simmons, Ernest Joseph, 1903-1972 (Vintage Russian library., 1946)
Simmons shows an equal mastery of detail and design. No other biography traces so clearly the course of Tolstoy's development, or makes the central cause of it so manifest. -- Cover.